The Energy Trilemma and the Alignment of Indonesian Nickel Policy - Indra Kusumawardhana; Octavia Adiel Permata (Journal of Governance, 2023)
This article examines the energy trilemma faced by Indonesia in the context of the nickel industry, focusing on three main aspects: the reliability of energy supply, environmental sustainability, and economic accessibility. With the global demand for nickel in electric vehicle batteries increasing, Indonesia, as one of the largest nickel producers, faces significant challenges in ensuring a stable, environmentally friendly, and affordable energy supply for nickel processing and extraction. The study uses data analysis from the mining and energy sectors to evaluate how current energy policies impact the nickel industry. It also explores the use of renewable energy sources in nickel mining operations and their impact on environmental sustainability. Furthermore, the article assesses the economic accessibility of the energy used in the nickel industry, considering the importance of nickel in the Indonesian economy. Findings indicate that despite progress in renewable energy utilization, challenges remain in production scalability and long-term sustainability. The article proposes strategies for optimizing energy resource management in the nickel industry, emphasizing the importance of technological innovation, supportive policies, and international cooperation. This research provides essential insights for policymakers, investors, and industry stakeholders in addressing the energy trilemma in Indonesia, particularly in the context of the evolving nickel industry.